Enhancing clinical practice in the management of distress: The Therapeutic Practices for Distress Management (TPDM) project. Issue 9 (31st July 2018) - McLeod, Deborah; Esplen, Mary Jane; Wong, Jiahui; Hack, Thomas F.; Fillion, Lise; Howell, Doris; Fitch, Margaret; Dufresne, Julie
Abstract: Objective: The Therapeutic Practices for Distress Management (TPDM) project was carried out to support clinicians in integrating recommendations from four clinical practice guidelines (CPGs) in routine care at five Pan Canadian cancer care sites. Methods: Using a concurrent, mixed‐method study design and knowledge translation (KT) activities, this project included two phases: phase I—a baseline/preparation phase and phase II—an intervention phase plus evaluation. The intervention phase (the focus of this report) included a one‐year education and supervision program (24 hours in virtual class; 12‐hour group supervision). Primary outcomes were knowledge and self‐efficacy in practicing CPGs as measured by a Knowledge and Self‐Efficacy Survey (KSES). A secondary outcome was observer‐rated performances with standardized patients (objective structured clinical exams). Participants included 80 (90%) nurses, and 9 (10%) social workers (N = 89). Results: The TPDM program was effective in accomplishing change in knowledge, self‐efficacy, and performance. All measures demonstrated significant change pre and post module, with evidence of increasing knowledge ( P  < .01) and confidence ( P  < .01) over time. Further, there was evidence of a shift in barriers and enablers to practicing in alignment with the CPGs. Conclusions: A tailored education program using case‐based learning and supervision over time improves knowledge and practice among front line clinicians. The findings have implications for quality improvement in cancer care.